The Influence of the Causalitik Learning Model Integrated with Local Wisdom Values Assisted by Articulate Storyline on Students' Creative Thinking Ability - Prasetiawati, Eka; Rokhmat, Joni; Hikmawati (International Journal of Contextual Science Education, 2025)
This study aims to examine the influence of the causalitic learning model integrated with local wisdom values, assisted by Articulate Storyline, to enhance students' creative thinking ability on the topic of sound waves The research employs a quasi-experimental design with a nonequivalent control group design. The population consists of eleventh-grade students at SMAN 2 Narmada for the 2025/2026 academic year. Sampling was conducted using cluster random sampling, resulting in the selection of 21 students from class XI-A as the experimental group and 20 students from class XI-C as the control group. The experimental group received treatment through the causalius, learning model integrated with local wisdom values, while the control group was treated conventionally. Data on creative thinking ability (CTA) were obtained through an essay test consisting of 5 questions. The average CTA scores were 82.07 for the experimental group and 77.33 for the control group. The data from both groups were homogeneous and normally distributed. The CTA data were analyzed using a pooled variance t-test The analysis vielded a calculated t-value of 2.19 and a table t-value at a 5% significance level of 2.023, resulting in salculated wable Therefore, it can be concluded that there is a significant influence of implementing the causalitic learning model integrated with local wisdom values, assisted by Articulate Storyline, on the creative thinking ability of high school students in the sound waves topic.